2023
DOI: 10.1021/acsmedchemlett.3c00127
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Pyrazole-Based Macrocyclic Kinase Inhibitors Targeting BMPR2

Abstract: Bone morphogenetic protein (BMP) signaling is mediated by transmembrane protein kinases that form heterotetramers consisting of type-I and type-II receptors. Upon BMP binding, the constitutively active type-II receptors activate specific type-I receptors by transphosphorylation, resulting in the phosphorylation of SMAD effector proteins. Drug discovery in the receptor tyrosine kinase-like (TKL) family has largely focused on type-I receptors, with few inhibitors that have been published targeting type-II recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…The detected G2M arrest at high compound concentration (10 μM), but not at 1 μM, may be due to inhibition of these off-targets. Macrocyclization is an excellent method achieving high kinome-wide selectivity which we and others demonstrated on several examples, 24,4143 including exclusive selectivity for oncogenic mutants over the wild-type protein. 44 The kinome-wide selectivity we achieved for JA310 ( 21c ) is remarkable compared with the promiscuous lead compound 1 used as starting point.…”
Section: Discussionmentioning
confidence: 91%
“…The detected G2M arrest at high compound concentration (10 μM), but not at 1 μM, may be due to inhibition of these off-targets. Macrocyclization is an excellent method achieving high kinome-wide selectivity which we and others demonstrated on several examples, 24,4143 including exclusive selectivity for oncogenic mutants over the wild-type protein. 44 The kinome-wide selectivity we achieved for JA310 ( 21c ) is remarkable compared with the promiscuous lead compound 1 used as starting point.…”
Section: Discussionmentioning
confidence: 91%
“…These hallmarks include sustaining proliferative signaling, deregulating cellular energetics, evading growth suppressors, and resisting cell death. Recent data showed that macrocycles also can target bone morphogenetic protein receptor type‐II (BMPR2) 67 and death‐associated protein kinase 1 (DRAK1) 68 for cancer therapy (Table 2). Therefore, macrocyclic molecules can block nearly 80% of cancer hallmarks to achieve cancer regression.…”
Section: Discussionmentioning
confidence: 99%
“… Chemical structures of BMPR-II inhibitors . The recently disclosed first-in-class BMPR2 (i.e., one of the three type II receptors) inhibitors CDD-1653 and Compound 8a feature a 2,4-diamino­pyrimidine core scaffold but are classified as distinct chemotypes based on their putatively different hinge-binding motifs. , …”
Section: Bmp Inhibitorsmentioning
confidence: 99%
“…The latest BMPR2 inhibitor is the macrocyclic pyrazole Compound 8a , which was designed by macrocyclization of a promiscuous, aminopyrazole-based kinase inhibitor . In addition to investigating the BMPR2 affinity (IC 50 = 506 nM), the overall kinome selectivity was assessed and suggested only FLT3 and GSK as relevant off-targets.…”
Section: Bmp Inhibitorsmentioning
confidence: 99%